Omega-3 fatty acids transport through the placenta (Asian Journal of Medical and Biological Research, 2016)
The placenta is a temporary vital organ for sustaining the development of the fetus throughout gestation. Although the fatty acid composition delivered to the fetus is largely determined by maternal circulating levels, the placenta preferentially transfers physiologically important long-chain polyunsaturated fatty acids (LC-PUFAs), particularly omega-3 (n-3) FAs. The precise mechanisms governing these transfers were covered in a veil, but have started to be revealed gradually. Several evidences suggest fatty acid transport proteins (FATPs), placental specific membrane bound fatty acid binding proteins (pFABPpm) and fatty acid translocases (FAT/CD36) involved in LC-PUFAs uptake. Our studies have shown that the placental transfer of omega-3 FAs through the trophoblast cells is largely contributed by fatty acid binding protein 3 (FABP3). Recently there are considerable interests in the potential for dietary omega-3 FAs as a therapeutic intervention for fetal disorders. In fact, prenatal supply of omega-3 FAs is essential for brain and retinal development. Recent findings suggest a potential opportunity of omega-3 FA interventions to decrease the incidence of type 2 diabetes in future generations. In this review, we discuss the molecular mechanism of transportation of omega-3 FAs through the placenta and how omega-3 FAs deficiency/supplementation impact on fetal development.Asian J. Med. Biol. Res. March 2016, 2(1): 1-8